A preparation process for modified nonwoven fabric produced by recycling PP lunch box fragments

By developing a modified non-woven fabric preparation process, including efficient cleaning, modification strengthening, melt homogenization and equipment optimization, many technical problems in recycling PP lunch box fragments in the production of non-woven fabrics have been solved, and efficient utilization, environmental protection and performance improvement have been achieved.

CN119221210BActive Publication Date: 2025-03-28SHANGHAI RE-POLY ENVIRONMENTAL PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411718621.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-28
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

In the prior art, there are many shortcomings when producing nonwoven fabrics using recycling of PP lunch boxes, including low raw material purity, unstable melt index, irregular material shape and odor residue, resulting in poor spinning stability, difficult processing control, difficult transportation and metrology, and the product does not meet the application requirements.

Method used

Develop a modified nonwoven fabric preparation process, including efficient cleaning and sorting, modification and strengthening treatment, melt homogenization and equipment optimization steps, to ensure the purity and performance of the recycled materials and meet the requirements of nonwoven fabric production. Specific measures include the use of twin-screw extruders, screw conveyors, dilute-phase pneumatic conveying systems, pretreatment and optimized pipeline design.

Benefits of technology

Through this process, the utilization efficiency of recycled PP lunch boxes is improved, the use and production costs of native PP are reduced, environmental pollution is effectively reduced, the recycling of plastic resources is realized, and the mechanical properties and antibacterial functions of non-woven fabrics are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119221210B_ABST
    Figure CN119221210B_ABST
Patent Text Reader

Abstract

The invention discloses a modified non-woven fabric preparation process produced by recycling PP lunch box broken pieces, belonging to the technical field of non-woven fabrics, and the process comprises the following steps: first, the recycled PP lunch box broken pieces are sorted, cleaned and screened, and then mixed with a modified reinforcing agent for standby use; then a spiral feeder is used to transport the prepared raw materials to a screw extruder for melt extrusion; then the melt is extruded through a spinneret for spinning and forming, and the fiber is cooled and solidified by a cooling device, and a continuous fiber web is formed after laying; finally, the fiber web is reinforced by drawing and thermal bonding, and a non-woven fabric with required physical properties is formed after laying, and heat treatment and calendering treatment are performed. This preparation process not only effectively utilizes the discarded PP lunch boxes, reduces the use of virgin PP, and reduces production costs, but also reduces environmental pollution, and has significant economic and social benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonwoven fabrics, and in particular relates to a process for preparing modified nonwoven fabrics produced by utilizing recycled PP lunch box fragments. Background Art

[0002] Polypropylene (PP) is one of the five general-purpose plastics with excellent physical and chemical properties, such as high strength and rigidity, good heat resistance and electrical insulation, excellent chemical resistance and steam permeation resistance. PP material is widely used in the fields of automobiles, home appliances, food packaging, medical and health care, etc. due to its low density, light weight, high design flexibility, green environmental protection, excellent performance and low manufacturing cost.

[0003] PP non-woven fabric is a non-woven sheet material made of PP as the main raw material through melt blowing, spinning and other processes. Compared with woven fabrics, PP non-woven fabrics have the advantages of light weight, high strength, good air permeability and low cost. They have broad application prospects in the fields of medical treatment, hygiene, filtration, etc. Traditional PP non-woven fabrics mostly use virgin PP slices or powder as raw materials, and put forward high requirements on the purity and melt index of PP raw materials. Recycling discarded PP lunch boxes to produce PP non-woven fabrics can not only reduce the use of virgin PP and reduce production costs, but also reduce the environmental load, which has significant economic and social benefits.

[0004] However, there are still many technical challenges in directly using recycled PP lunch boxes for non-woven fabric production:

[0005] Recycled PP lunch boxes have low purity and contain other plastics such as PE, as well as impurities such as paper scraps and metals, which affect the spinning stability;

[0006] The melt index of recycled PP lunch boxes is high and fluctuates greatly, which is not conducive to spinning process control;

[0007] The recycled PP lunch box fragments have irregular shapes and low bulk density, which can easily cause difficulties in transportation and metering;

[0008] Recycled PP lunch boxes are prone to residual odor and require further deodorization to meet application requirements in areas such as sanitary materials.

[0009] Therefore, it is urgent to develop a systematic recycling process, including efficient cleaning and sorting of recycled PP lunch boxes, modification and capacity expansion, melt homogenization, equipment optimization, etc., to solve the technical bottleneck of recycled PP lunch box fragments in non-woven fabric production, realize their high-value and large-scale utilization, and promote the development of plastic circular economy. This is of great significance for reducing the consumption of primary resources, alleviating environmental pollution pressure, and promoting the green and sustainable development of the industry. Summary of the invention

[0010] 1. Problems to be solved

[0011] The present invention aims to solve the multiple deficiencies in the prior art when using recycled PP lunch box fragments to produce non-woven fabrics. The main problems include:

[0012] Low purity of raw materials: Recycled PP lunch boxes usually contain impurities such as other plastics, paper scraps, metals, etc. These impurities will affect the spinning stability and product quality.

[0013] Unstable melt index: The melt index of recycled PP lunch boxes is high and fluctuates greatly, making it difficult to control the spinning process.

[0014] Irregular material shape: The irregular shape of the crushed pieces and low bulk density make transportation and metering difficult.

[0015] Residual odor: Recycled PP lunch boxes may have residual odor and need further processing to meet application requirements.

[0016] The present invention aims to improve the utilization efficiency of recycled PP lunch boxes by developing a modified non-woven fabric preparation process. The process includes the steps of efficient cleaning and sorting, modification and strengthening treatment, melt homogenization and equipment optimization to ensure the purity and performance of the recycled materials and meet the requirements of non-woven fabric production. This can not only reduce the use of virgin PP and reduce production costs, but also effectively reduce environmental pollution, realize the recycling of plastic resources, and promote green and sustainable development.

[0017] 2. Technical solution

[0018] To solve the above problems, the technical solution provided by the present invention is:

[0019] A process for preparing a modified nonwoven fabric produced by recycling PP lunch box fragments comprises the following steps:

[0020] (1) Raw material preparation: sort, clean and screen the recycled PP lunch box fragments, then mix them with the modified enhancer for later use;

[0021] Figure 1 The conventional spunbond nonwoven production process was demonstrated. Recycling PP lunch box fragments to directly produce spunbond nonwovens (direct spinning) is a new type of high-value utilization technology for recycled polypropylene materials. Its production process is simplified, which is different from traditional weaving, flat wire drawing and other processes. The specific differences are as follows:

[0022] Different process principles

[0023] Direct spinning: The recycled PP crushed material is melted by the screw and directly extruded through the spinneret, cooled and stretched to form filaments, and then laid to form non-woven fabrics. This is a typical melt spinning process.

[0024] Wire drawing: PP melt is extruded into film or thick wire, and then stretched into thin wire. Wire drawing is an independent process after extrusion molding in weaving and flat wire processes.

[0025] Different device configurations

[0026] Direct spinning: The main equipment includes screw extruder, spinneret, cooling and drawing device, laying device, etc. The process is short and the equipment is relatively simple.

[0027] Wire drawing: In addition to the extruder, special stretching equipment such as drawing machines, winding machines, etc. are also required. The process is long and the equipment is complex.

[0028] Different product forms

[0029] Direct spinning: The product is a directional or randomly arranged fiber web that can be directly used for non-woven fabrics.

[0030] Wire drawing: The product is a continuous filament that needs to be made into fabric or non-woven fabric through weaving or needle punching.

[0031] Different fiber fineness

[0032] Direct spinning: The fiber fineness is 1~3 dtex, which is medium-fine denier.

[0033] Wire drawing: The fiber fineness is generally >3 dtex, mostly coarse denier yarns.

[0034] Different production efficiency

[0035] Direct spinning: short production process, spinning speed up to 3000 m / min or more, high production efficiency.

[0036] Wire drawing: many processes, complex equipment and relatively low production efficiency.

[0037] Different product performance

[0038] Direct spinning: The fiber fineness is evenly distributed, the non-woven fabric feels soft and has slightly lower strength.

[0039] Wire drawing: The wire strength is high and the fabric has excellent mechanical properties, but the softness is poor.

[0040] Therefore, using recycled PP lunch box fragments to directly produce spunbond nonwovens can simplify the process, reduce production costs, improve production efficiency, and give recycled PP new high value-added uses; this is of great significance for promoting plastic recycling and developing a circular economy; however, the direct spinning process also places higher requirements on raw material purity and melt uniformity, so optimizing raw material formulation and process control are the key to the industrial application of this technology.

[0041] (2) Feeding and conveying: using a screw feeder to convey the raw materials prepared in step (1) to the screw extruder;

[0042] During our use, it is recommended to use the feeder model 51 / 80 from Zhangjiagang Lingang Machinery Co., Ltd., with a motor of 2.2 (KW).

[0043] In general, the following optimization schemes are proposed:

[0044] Use twin-screw extruders instead of single-screw extruders: Twin-screw extruders have stronger propulsion and mixing and dispersing capabilities, which can effectively overcome the feeding difficulties caused by low bulk density and irregular shapes of broken pieces. The staggered meshing design of the twin screws helps to agglomerate the broken materials, improve melt uniformity, and reduce bubble generation. Use side feeding or multi-point feeding to prevent the material from falling directly into the screw space and bringing in air. Set a filling device at the feeding port to ensure that the material is fed tightly and reduce air entry.

[0045] Through the above optimization measures, the problems of low bulk density, difficulty in feeding, melt bubbles, etc. in the application of recycled PP lunch box fragments in spunbond non-woven production lines can be effectively solved, the output and product quality can be improved, and the high-value utilization of resources can be achieved. In the specific implementation, it is also necessary to optimize the combination and adaptability according to the equipment conditions and material characteristics.

[0046] For feeding and conveying, the suggestions and measures are as follows:

[0047] Use screw conveyor: Due to the low bulk density and irregular shape of recycled PP lunch box fragments, the traditional vacuum suction system is prone to "bridging" and cause feeding blockage. You can use a screw conveyor instead. Its spiral design can better handle low-density and irregular-shaped materials and reduce the occurrence of "bridging".

[0048] Pneumatic conveying system: Consider using a dilute phase pneumatic conveying system, which is suitable for handling lower density materials and can effectively convey irregular shaped fragments by adjusting the air flow rate and pressure.

[0049] Material pretreatment:

[0050] Add pretreatment steps: Before conveying, the recycled PP lunch box fragments are pretreated, such as further crushing or granulation, to increase the bulk density and uniformity. This can reduce the risk of blockage during the conveying process.

[0051] Pipeline design:

[0052] Optimize pipeline design: Design a wider delivery pipeline or increase the bending radius to reduce material blockage in the pipeline. Ensure that the inner wall of the pipeline is smooth to reduce friction resistance.

[0053] Install vibrating devices: Install vibrating devices at key locations in the conveying pipeline to help prevent material accumulation and blockage.

[0054] Real-time monitoring and adjustment:

[0055] Real-time monitoring system: Install sensors and monitoring systems to detect flow and pressure changes during the conveying process in real time, and adjust the conveying parameters in time to avoid blockage.

[0056] Automated Control: Use automated systems to adjust conveying speed and airflow based on real-time monitoring data to optimize conveying efficiency.

[0057] Mixing and Homogenization:

[0058] Homogenization: Before conveying, the crushed pieces from different sources are mixed to ensure the uniformity and consistency of the material, thereby reducing the flow instability problems that occur during conveying.

[0059] Through the above optimization measures, the conveying efficiency of recycled PP lunch box fragments in the production of spunbond non-woven fabrics can be effectively improved, blockage and downtime can be reduced, thereby improving the overall production efficiency and product quality.

[0060] (3) Screw extrusion: using a screw extruder to melt and extrude the raw materials in step (2);

[0061] The above process steps can effectively solve the problems of insufficient feeding and melt bubbles in the application of recycled PP lunch box fragments in spunbond nonwoven production lines, improve production and product quality, and achieve high-value utilization of resources. In the specific implementation, it is also necessary to optimize the combination and adaptability according to equipment conditions and material characteristics.

[0062] (4) Spinning: Extruding the melt-extruded material in step (3) through a spinneret for spinning;

[0063] (5) Cooling and solidifying: cooling and solidifying the fibers spun in step (4) by a cooling device, and forming a continuous fiber web after laying;

[0064] (6) stretching and consolidation: stretching the fiber web obtained in step (5), and then forming a nonwoven fabric with desired physical properties by thermal bonding and web laying;

[0065] (7) Post-treatment: heat treatment and calendering treatment are performed on the non-woven fabric obtained in step (6).

[0066] Preferably, the sorting step in step (1) is as follows: pouring the PP lunch box broken pieces into clean water, stirring and separating the floating PP lunch box broken pieces; the cleaning step in step (1) is as follows: putting the sorted PP lunch box broken pieces into 60℃-80℃ hot water, stirring and cleaning; the screening step in step (1) is as follows: controlling the size of the cleaned PP lunch box broken pieces to within 10mm by a crusher.

[0067] There are several key aspects to consider:

[0068] Raw material purity and composition control:

[0069] Purity requirements: Ensure that the non-PP content of the recycled PP lunch box fragments is less than 3%. This helps to improve the stability of the spinning process and reduce the impact of impurities on equipment wear and product quality.

[0070] Composition uniformity: By mixing recycled materials from different batches, the impact of the melt index fluctuation of a single recycled material can be reduced, thereby stabilizing the melt index of the overall recycled material and facilitating spinning.

[0071] Melt Flow Index (MFI) Control:

[0072] Target range: Use PP raw materials with a melt index of 25-40 g / 10min to ensure good melt flow and spinning performance.

[0073] Melt index adjustment: The melt index can be adjusted by adding modifiers or mixing PP materials with different melt indexes to make it suitable for the production requirements of spunbond nonwoven fabrics.

[0074] Impurity treatment:

[0075] Impurity removal: Recycled PP lunch boxes are strictly sorted and cleaned to remove impurities such as film, paper scraps, metal, etc., to prevent clogging of the filter and spinneret.

[0076] Filtration system: A multi-stage filtration system is used during the melt extrusion process to further remove residual tiny impurities.

[0077] Molecular weight distribution:

[0078] Uniformity control: Select PP raw materials with narrow molecular weight distribution to improve spinning stability and mechanical properties of products.

[0079] Modification treatment: By adding compatibilizers and toughening agents to PP, the molecular weight distribution is improved and the toughness and impact resistance of the material are enhanced.

[0080] Process Optimization:

[0081] Temperature control: During the screw extrusion and spinning process, the temperature of each zone is precisely controlled to ensure full melting and uniform mixing of PP.

[0082] Equipment adjustment: According to the characteristics of the raw materials, adjust the screw design and extrusion equipment to meet the processing requirements of recycled PP.

[0083] Through the above measures, the raw material problem of recycled PP lunch box fragments in the production of spunbond non-woven fabrics can be effectively solved, product quality can be improved, production costs can be reduced, and the recycling of plastics can be promoted.

[0084] The modified nonwoven fabric preparation process produced by recycling PP lunch box fragments,

[0085] In step (1), the added mass of the modified strengthening agent is 10%-15% of the PP lunch box crushed pieces;

[0086] The components of the modified reinforcing agent in step (1) include the following in parts by weight:

[0087] 25-40 parts of aminoacetic acid,

[0088] 10-20 parts of nanocomposite materials,

[0089] 5-10 parts of azobisisobutyronitrile,

[0090] 15-25 parts of polyethylene glycol;

[0091] The mixing pressure in step (1) is 2MPa-4MPa, and the mixing temperature is 65°C-75°C.

[0092] The modified nonwoven fabric preparation process produced by recycling PP lunch box fragments,

[0093] The preparation method of the nanocomposite material is as follows:

[0094] The mass ratio of magnesium nitrate, ferrous sulfate, gadolinium nitrate, manganese nitrate and triacetylacetonate cobalt is (1-5): (1-5): (3-6): (2-8): (1-6) and then ground and mixed. 50-80 times the mass of imidazole-4-carboxylic acid of the mixture is added, and the mixture is stirred at 80-90°C for 8h-16h. The precipitate is repeatedly washed with anhydrous ethanol, and then vacuum freeze-dried at -80°C for 24h. The obtained powder is transferred to a high-temperature calcining furnace and calcined at 400-600°C for 9h-13h under a nitrogen environment, wherein the heating rate is 10°C / min. For this part, the amount of the modified reinforcing agent is 10%-15% of the PP lunch box broken pieces, indicating that its amount is not much but the effect is significant. The modified reinforcing agent contains: nanocomposite materials (10-20 parts): nanoparticles have the characteristics of large specific surface area and high surface energy, which can form strong interfacial forces with PP and play a role in volume expansion and reinforcement. Azobisisobutyronitrile (5-10 parts): a commonly used free radical initiator. Polyethylene glycol (15-25 parts): a hydrophilic polymer that can improve the hydrophilicity and antistatic properties of PP. The mixed modification process is carried out under high pressure of 2-4MPa and temperature of 65-75℃, which is conducive to promoting the melt blending and chemical reaction of PP and the modified components. The preparation process of nanocomposite materials is complicated. After multiple steps such as mixing and grinding, solvent thermal reaction, freeze drying, and high temperature calcination, it can be seen that its structure and properties have been finely controlled and it is a high-performance functional filler. In summary, the modified reinforcing agent can significantly improve the polarity, compatibility, mechanical properties and functionality of the recycled PP lunch box fragments through physical blending and chemical grafting reactions, so that it can meet the production requirements of spunbond non-woven fabrics. Therefore, the rational use of modified reinforcing agents is one of the core points of this invention.

[0095] At the same time, for nanocomposites (high-entropy nanozymes), antibacterial effects can be achieved. Specifically, high-entropy nanozymes are a new type of multi-component nanocomposites, which are formed by compounding five or more metal elements in nearly equiatomic proportions. This multi-component composite strategy breaks the component limitations of traditional nanozymes and provides greater space for the performance regulation of nanozymes.

[0096] High-entropy nanozymes have the characteristics of both high-entropy alloys and nanozymes. On the one hand, the high-entropy effect makes nanoparticles have a more uniform element distribution, a more stable structure and a smaller size; on the other hand, the nanozyme effect gives the material excellent biocatalytic properties, such as peroxidase and oxidase activities.

[0097] In the field of antibacterial, high-entropy nanozymes mainly play a role through peroxidase-like activity. They can catalyze hydrogen peroxide (H2O2) to produce highly active hydroxyl radicals (·OH), which cause oxidative damage to bacteria, destroy bacterial cell membranes, proteins and DNA, and ultimately lead to bacterial death.

[0098] Compared with traditional single or binary component nanozymes, high-entropy nanozymes exhibit higher peroxidase activity and a broader spectrum of antibacterial effects, thanks to the synergistic catalysis brought about by the high-entropy effect and the exposure of more active sites.

[0099] In addition, by adjusting the components, proportions, morphology and size of high-entropy nanozymes, their enzymatic properties and antibacterial effects can be further optimized. For example, by doping some elements with photothermal effects, photothermal-enzymatic synergistic antibacterial effects can be achieved; by introducing some ligands with specific binding ability, the selectivity and targeting of antibacterial effects can be improved.

[0100] At present, although high-entropy nanozymes have shown good application prospects in the antibacterial field, there are still some problems to be solved, such as biosafety assessment of materials, in-depth research on antibacterial mechanisms, optimization of preparation processes, and exploration of large-scale applications.

[0101] In summary, as a new type of nanocomposite material, high-entropy nanozymes have brought new research ideas and applications to the antibacterial field. By leveraging the advantages of multi-component synergy and nanozyme catalysis, high-entropy nanozymes are expected to become a new type of highly efficient, broad-spectrum, and long-lasting antibacterial agent, with broad application prospects in medical devices, wound dressings, and antifouling coatings. In the future, high-entropy nanozymes are expected to be combined with other antibacterial technologies to develop more intelligent and precise antibacterial strategies.

[0102] The modified nonwoven fabric preparation process produced by recycling PP lunch box fragments,

[0103] The screw feeder described in step (2) is a screw conveyor, and its pitch is 0.5 to 0.6 times the screw diameter.

[0104] The modified nonwoven fabric preparation process produced by recycling PP lunch box fragments,

[0105] The parameters of melt extrusion in step (3) are as follows:

[0106] Zone 1: 215-225℃,

[0107] Zone 2: 220-230℃,

[0108] Zone 3: 225-235℃,

[0109] Zone 4: 230-240℃,

[0110] Zone 5: 235-245℃,

[0111] Zone VI: 230-240℃.

[0112] The modified nonwoven fabric preparation process produced by recycling PP lunch box fragments,

[0113] The aperture of the spinneret in step (4) is 0.2-0.4 mm;

[0114] In step (4), the temperature of the spinneret is 280-300°C;

[0115] In step (4), the spinning speed of the spinneret is 1500-3500 m / min;

[0116] The fiber fineness range of the spun fiber in step (4) is 1.0-2.5 dtex.

[0117] The modified nonwoven fabric preparation process produced by recycling PP lunch box fragments,

[0118] The cooling range of the cooling and curing in step (5) is 5°C / min;

[0119] The final temperature after cooling and solidification in step (5) is 25°C;

[0120] The ambient humidity during cooling and curing in step (5) is 60%.

[0121] The modified nonwoven fabric preparation process produced by recycling PP lunch box fragments,

[0122] The parameters for drafting in step (6) are as follows:

[0123] The drafting ratio is 1.2-3.5 times, the drafting temperature is 40-60℃, and the drafting speed is 80-150 m / min;

[0124] The parameters for hot bonding in step (6) are as follows:

[0125] The method is hot rolling, the roll temperature is 140-160°C, the roll pressure is 40-80 N / mm, and the roll gap is 0.1-1.0mm.

[0126] In the process for preparing the modified nonwoven fabric produced by recycling PP lunch box fragments, the parameters of the heat treatment in step (7) are as follows:

[0127] The temperature is 130-160°C and the heat treatment time is 30-120s;

[0128] The parameters of the calendering treatment in step (7) are as follows:

[0129] The calendering temperature is 100-140°C, the calendering pressure is 20-100 N / mm, the calendering time is 2-10s, and the calendering roller linear speed is 10-100 m / min.

[0130] 3. Beneficial effects

[0131] Resource recycling: By using recycled PP lunch box fragments as raw materials, the demand for virgin polypropylene is reduced, production costs are reduced, and the impact of plastic waste on the environment is effectively reduced.

[0132] Improved product performance: After adding modified reinforcing agents, the mechanical properties of non-woven fabrics, including tensile strength, tear strength and elongation at break, are significantly improved. These modifiers improve the polarity and compatibility of the material, enhance the bonding force between fibers, and thus improve the overall performance of the product.

[0133] Process optimization: This preparation process ensures the purity and uniformity of the recycled materials through sorting, cleaning, screening and other steps, optimizes the melt extrusion and spinning molding processes, and improves production efficiency and product quality.

[0134] Antibacterial properties: Through the use of nanocomposites, non-woven fabrics are given antibacterial properties, which effectively inhibits bacterial growth and enhances the application value of the product in medical and health fields.

[0135] Environmental friendliness: The entire process reduces the generation of waste and the difficulty of treatment, meets the requirements of green manufacturing and sustainable development, and helps reduce the burden of plastics on the environment.

[0136] In summary, the present invention not only realizes the high-value utilization of discarded PP lunch boxes, but also improves the performance and application scope of non-woven fabrics through technological innovation, and has significant economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0137] Figure 1 This is a process flow chart of conventional spunbond nonwoven fabric production;

[0138] Figure 2 It is a structural principle diagram of the nanocomposite material in the present invention;

[0139] Figure 3 This is a high-resolution transmission electron microscope (HRTEM) image of the nanocomposite material prepared in Scheme 3 of the present invention;

[0140] Figure 4 It is an electron paramagnetic resonance spectrum (EPR) diagram of the nanocomposite material prepared in scheme 3 of the present invention;

[0141] Figure 5 This is a graph of the antibacterial survival rate of the nonwoven fabrics prepared in Schemes 1-5 of the present invention. DETAILED DESCRIPTION

[0142] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0143] It should be noted that, in the present invention, all weight parts or proportion values ​​involved are based on the international standard unit kilogram (Kg).

[0144] At the same time, the recycled PP lunch box fragments come from disposable takeaway lunch boxes. The manufacturer is Sichuan Hongchang Plastic Industry Co., Ltd., the product number is HC092327, brand: Maryya / Maryya, material: polypropylene (PP).

[0145] Solution 1

[0146] The preparation process of modified non-woven fabric produced by recycling PP lunch box broken pieces includes the following steps:

[0147] (1) Raw material preparation: sort, clean and screen the recycled PP lunch box fragments, then mix them with the modified enhancer for later use;

[0148] Specifically, the sorting step in step (1) is as follows: pour the PP lunch box crushed pieces into clean water, stir and separate the floating PP lunch box crushed pieces; the cleaning step in step (1) is as follows: put the sorted PP lunch box crushed pieces into 60°C hot water, stir and clean; the screening step in step (1) is as follows: control the size of the cleaned PP lunch box crushed pieces within 10 mm through a crusher.

[0149] The mass of the modified strengthening agent added in step (1) is 10% of the PP lunch box crushed pieces;

[0150] The components of the modified reinforcing agent in step (1) include the following in parts by weight:

[0151] 25 parts of aminoacetic acid,

[0152] 20 parts of nanocomposite materials,

[0153] 5 parts of azobisisobutyronitrile,

[0154] 25 parts of polyethylene glycol;

[0155] The mixing pressure in step (1) is 2 MPa and the mixing temperature is 75°C.

[0156] The preparation method of the nanocomposite material is as follows:

[0157] Magnesium nitrate, ferrous sulfate, gadolinium nitrate, manganese nitrate and cobalt triacetylacetonate are ground and mixed in a mass ratio of 1:5:3:8:1, imidazole-4-carboxylic acid in an amount 50 times the mass of the mixture is added, and the mixture is stirred and reacted at 80°C for 16 hours. The precipitate is repeatedly rinsed with anhydrous ethanol, and then vacuum freeze-dried at -80°C for 24 hours. The obtained powder is transferred to a high-temperature calcination furnace and calcined at 400°C for 13 hours under a nitrogen environment, with a heating rate of 10°C / min.

[0158] (2) Feeding and conveying: using a screw feeder to convey the raw materials prepared in step (1) to the screw extruder;

[0159] Specifically, the screw feeder described in step (2) is a screw conveyor, and its pitch is 0.5 times the screw diameter.

[0160] (3) Screw extrusion: using a screw extruder to melt and extrude the raw materials in step (2);

[0161] The parameters of melt extrusion in step (3) are as follows:

[0162] Zone 1: 215℃,

[0163] Zone 2: 230℃,

[0164] Zone 3: 225℃,

[0165] Zone 4: 240℃,

[0166] Zone 5: 235℃,

[0167] Zone 6: 240℃.

[0168] (4) Spinning: Extruding the melt-extruded material in step (3) through a spinneret for spinning;

[0169] Specifically, the aperture of the spinneret in step (4) is 0.2 mm; the temperature of the spinneret in step (4) is 300° C.; the spinning speed of the spinneret in step (4) is 1500 m / min; and the fiber fineness range of the spun fiber in step (4) is 2.5 dtex.

[0170] (5) Cooling and solidifying: cooling and solidifying the fibers spun in step (4) by a cooling device, and forming a continuous fiber web after laying;

[0171] Specifically, the temperature reduction range of the cooling and curing in step (5) is 5°C / min; the termination temperature after cooling and curing in step (5) is 25°C; and the ambient humidity of the cooling and curing in step (5) is 60%.

[0172] (6) stretching and consolidation: stretching the fiber web obtained in step (5), and then forming a nonwoven fabric with desired physical properties by thermal bonding and web laying;

[0173] Specifically, the parameters of the stretching in step (6) are as follows: the stretching ratio is 1.2 times, the stretching temperature is 60°C, and the stretching speed is 80 m / min; the parameters of the hot bonding in step (6) are as follows: the method is hot rolling, the roller temperature is 140°C, the roller pressure is 80 N / mm, and the roller gap is 0.1 mm.

[0174] (7) Post-treatment: heat treating and calendering the nonwoven fabric obtained in step (6);

[0175] Specifically, the parameters of the heat treatment in step (7) are as follows: temperature is 130°C, heat treatment time is 120s;

[0176] The parameters of the calendering treatment in step (7) are as follows: the calendering temperature is 100°C, the calendering pressure is 100 N / mm, the calendering time is 2s, and the calendering roller linear speed is 100 m / min.

[0177] Solution 2

[0178] The preparation process of modified non-woven fabric produced by recycling PP lunch box broken pieces includes the following steps:

[0179] (1) Raw material preparation: sort, clean and screen the recycled PP lunch box fragments, then mix them with the modified enhancer for later use;

[0180] Specifically, the sorting step in step (1) is as follows: pour the PP lunch box crushed pieces into clean water, stir and separate the floating PP lunch box crushed pieces; the cleaning step in step (1) is as follows: put the sorted PP lunch box crushed pieces into 80°C hot water, stir and clean; the screening step in step (1) is as follows: control the size of the cleaned PP lunch box crushed pieces within 10 mm through a crusher.

[0181] The mass of the modified strengthening agent added in step (1) is 15% of the PP lunch box crushed pieces;

[0182] The components of the modified reinforcing agent in step (1) include the following in parts by weight:

[0183] 40 parts of aminoacetic acid,

[0184] 10 parts of nanocomposite materials,

[0185] 10 parts of azobisisobutyronitrile,

[0186] 15 parts of polyethylene glycol;

[0187] The mixing pressure in step (1) is 4 MPa and the mixing temperature is 65°C.

[0188] The preparation method of the nanocomposite material is as follows:

[0189] Magnesium nitrate, ferrous sulfate, gadolinium nitrate, manganese nitrate and cobalt triacetylacetonate are ground and mixed in a mass ratio of 5:1:6:2:6, and 80 times the mass of imidazole-4-carboxylic acid of the mixture are added, and the mixture is stirred and reacted at 90°C for 8 hours. The precipitate is repeatedly rinsed with anhydrous ethanol, and then vacuum freeze-dried at -80°C for 24 hours. The obtained powder is transferred to a high-temperature calcination furnace and calcined at 600°C for 9 hours under a nitrogen environment, with a heating rate of 10°C / min.

[0190] (2) Feeding and conveying: using a screw feeder to convey the raw materials prepared in step (1) to the screw extruder;

[0191] Specifically, the screw feeder described in step (2) is a screw conveyor, and its pitch is 0.6 times the screw diameter.

[0192] (3) Screw extrusion: using a screw extruder to melt and extrude the raw materials in step (2);

[0193] The parameters of melt extrusion in step (3) are as follows:

[0194] Zone 1: 225℃,

[0195] Zone 2: 220℃,

[0196] Zone 3: 235℃,

[0197] Zone 4: 230℃,

[0198] Zone 5: 245°C,

[0199] Zone 6: 230℃.

[0200] (4) Spinning: Extruding the melt-extruded material in step (3) through a spinneret for spinning;

[0201] Specifically, the aperture of the spinneret in step (4) is 0.4 mm; the temperature of the spinneret in step (4) is 280° C.; the spinning speed of the spinneret in step (4) is 3500 m / min; and the fiber fineness range of the spun fiber in step (4) is 1.0 dtex.

[0202] (5) Cooling and solidifying: cooling and solidifying the fibers spun in step (4) by a cooling device, and forming a continuous fiber web after laying;

[0203] Specifically, the temperature reduction range of the cooling and curing in step (5) is 5°C / min; the termination temperature after cooling and curing in step (5) is 25°C; and the ambient humidity of the cooling and curing in step (5) is 60%.

[0204] (6) stretching and consolidation: stretching the fiber web obtained in step (5), and then forming a nonwoven fabric with desired physical properties by thermal bonding and web laying;

[0205] Specifically, the parameters of the stretching in step (6) are as follows: the stretching ratio is 3.5 times, the stretching temperature is 40°C, and the stretching speed is 150 m / min; the parameters of the hot bonding in step (6) are as follows: the method is hot rolling, the roller temperature is 160°C, the roller pressure is 40 N / mm, and the roller gap is 1.0 mm.

[0206] (7) Post-treatment: heat treating and calendering the nonwoven fabric obtained in step (6);

[0207] Specifically, the parameters of the heat treatment in step (7) are as follows: temperature is 160°C, heat treatment time is 30s;

[0208] The parameters of the calendering treatment in step (7) are as follows: the calendering temperature is 140°C, the calendering pressure is 20 N / mm, the calendering time is 10s, and the calendering roller linear speed is 10 m / min.

[0209] Solution 3

[0210] The preparation process of modified non-woven fabric produced by recycling PP lunch box broken pieces includes the following steps:

[0211] (1) Raw material preparation: sort, clean and screen the recycled PP lunch box fragments, then mix them with the modified enhancer for later use;

[0212] Specifically, the sorting step in step (1) is as follows: pour the PP lunch box crushed pieces into clean water, stir and separate the floating PP lunch box crushed pieces; the cleaning step in step (1) is as follows: put the sorted PP lunch box crushed pieces into 70°C hot water, stir and clean; the screening step in step (1) is as follows: control the size of the cleaned PP lunch box crushed pieces within 10 mm through a crusher.

[0213] The added mass of the modified strengthening agent in step (1) is 13% of the PP lunch box crushed pieces;

[0214] The components of the modified reinforcing agent in step (1) include the following in parts by weight:

[0215] 32 parts of aminoacetic acid,

[0216] 15 parts of nanocomposite materials,

[0217] 8 parts of azobisisobutyronitrile,

[0218] 20 parts of polyethylene glycol;

[0219] The mixing pressure in step (1) is 3 MPa and the mixing temperature is 70°C.

[0220] The preparation method of the nanocomposite material is as follows:

[0221] Magnesium nitrate, ferrous sulfate, gadolinium nitrate, manganese nitrate and cobalt triacetylacetonate are ground and mixed in a mass ratio of 3:3:5:5:3, imidazole-4-carboxylic acid in an amount of 65 times the mass of the mixture is added, and the mixture is stirred and reacted at 85°C for 12 hours. The precipitate is repeatedly rinsed with anhydrous ethanol, and then vacuum freeze-dried at -80°C for 24 hours. The obtained powder is transferred to a high-temperature calcination furnace and calcined at 500°C for 11 hours under a nitrogen environment with a heating rate of 10°C / min.

[0222] like Figure 2 As shown in FIG. 1 , it shows the structure of the nanocomposite material, showing a uniform structure, indicating that the five metal elements have a sufficiently uniform structure, thereby playing a catalytic role. Figure 3 As shown in Figure 2, all three regions show that the nanocomposite material presents a crystalline structure with an average lattice spacing of 0.220 nm. Figure 4 As shown, the intensity ratio of the four EPR signal peaks of the prepared nanocomposite material is 1:2:2:1, which proves that •OH is the main free radical produced in the catalytic process. Among them, DMPO: 5,5-dimethyl-1-pyrroline N-oxide (5,5-Dimethyl-1-pyrroline N-oxide) is a commonly used spin trapping agent used to capture short-lived free radicals. •OH: Hydroxyl Radical, a highly reactive oxidizing free radical, widely participates in oxidation reactions. In the EPR (electron paramagnetic resonance) experiment, DMPO reacts with hydroxyl radicals (•OH) to form a stable free radical adduct (DMPO-OH), so that the presence and concentration of hydroxyl radicals can be detected by EPR spectroscopy. This method is often used to study oxidative stress, free radical reaction mechanisms, and the effects of antioxidants. •OH is an extremely strong oxidant with very high reactivity. It can react with a variety of biological macromolecules in bacteria, including proteins, nucleic acids, lipids, etc. Killing effect on bacteria: • OH can induce lipid peroxidation to destroy the bacterial cell membrane structure and damage DNA: • OH can attack DNA molecules to cause DNA chain breaks and base damage, • OH can oxidize amino acid residues in proteins to cause protein denaturation and inactivation, and by destroying key enzymes and metabolites • OH can interfere with the normal metabolic process of bacteria.

[0223] (2) Feeding and conveying: using a screw feeder to convey the raw materials prepared in step (1) to the screw extruder;

[0224] Specifically, the screw feeder described in step (2) is a screw conveyor, and its pitch is 0.5 times the screw diameter.

[0225] (3) Screw extrusion: using a screw extruder to melt and extrude the raw materials in step (2);

[0226] The parameters of melt extrusion in step (3) are as follows:

[0227] Zone 1: 215℃,

[0228] Zone 2: 220℃,

[0229] Zone 3: 225℃,

[0230] Zone 4: 230℃,

[0231] Zone 5: 235℃,

[0232] Zone 6: 230℃.

[0233] (4) Spinning: Extruding the melt-extruded material in step (3) through a spinneret for spinning;

[0234] Specifically, the aperture of the spinneret in step (4) is 0.3 mm; the temperature of the spinneret in step (4) is 290° C.; the spinning speed of the spinneret in step (4) is 2500 m / min; and the fiber fineness range of the spun fiber in step (4) is 2 dtex.

[0235] (5) Cooling and solidifying: cooling and solidifying the fibers spun in step (4) by a cooling device, and forming a continuous fiber web after laying;

[0236] Specifically, the temperature reduction range of the cooling and curing in step (5) is 5°C / min; the termination temperature after cooling and curing in step (5) is 25°C; and the ambient humidity of the cooling and curing in step (5) is 60%.

[0237] (6) stretching and consolidation: stretching the fiber web obtained in step (5), and then forming a nonwoven fabric with desired physical properties by thermal bonding and web laying;

[0238] Specifically, the parameters of the stretching in step (6) are as follows: the stretching multiple is 2 times, the stretching temperature is 50°C, and the stretching speed is 120 m / min; the parameters of the hot bonding in step (6) are as follows: the method is hot rolling, the roller temperature is 150°C, the roller pressure is 60N / mm, and the roller gap is 0.5 mm.

[0239] (7) Post-treatment: heat treating and calendering the nonwoven fabric obtained in step (6);

[0240] Specifically, the parameters of the heat treatment in step (7) are as follows: temperature is 150°C, heat treatment time is 100s;

[0241] The parameters of the calendering treatment in step (7) are as follows: the calendering temperature is 120°C, the calendering pressure is 60 N / mm, the calendering time is 5s, and the calendering roller linear speed is 60 m / min.

[0242] Solution 4

[0243] The preparation process of modified non-woven fabric produced by recycling PP lunch box broken pieces includes the following steps:

[0244] (1) Raw material preparation: sorting, cleaning and screening the recycled PP lunch box fragments;

[0245] Specifically, the sorting step in step (1) is as follows: pour the PP lunch box crushed pieces into clean water, stir and separate the floating PP lunch box crushed pieces; the cleaning step in step (1) is as follows: put the sorted PP lunch box crushed pieces into 60°C hot water, stir and clean; the screening step in step (1) is as follows: control the size of the cleaned PP lunch box crushed pieces within 10 mm through a crusher.

[0246] (2) Feeding and conveying: using a screw feeder to convey the raw materials prepared in step (1) to the screw extruder;

[0247] Specifically, the screw feeder described in step (2) is a screw conveyor, and its pitch is 0.5 times the screw diameter.

[0248] (3) Screw extrusion: using a screw extruder to melt and extrude the raw materials in step (2);

[0249] The parameters of melt extrusion in step (3) are as follows:

[0250] Zone 1: 225℃,

[0251] Zone 2: 230℃,

[0252] Zone 3: 235℃,

[0253] Zone 4: 240℃,

[0254] Zone 5: 245°C,

[0255] Zone 6: 240℃.

[0256] (4) Spinning: Extruding the melt-extruded material in step (3) through a spinneret for spinning;

[0257] Specifically, the aperture of the spinneret in step (4) is 0.2 mm; the temperature of the spinneret in step (4) is 300° C.; the spinning speed of the spinneret in step (4) is 1500 m / min; and the fiber fineness range of the spun fiber in step (4) is 1.0 dtex.

[0258] (5) Cooling and solidifying: cooling and solidifying the fibers spun in step (4) by a cooling device, and forming a continuous fiber web after laying;

[0259] Specifically, the temperature reduction range of the cooling and curing in step (5) is 5°C / min; the termination temperature after cooling and curing in step (5) is 25°C; and the ambient humidity of the cooling and curing in step (5) is 60%.

[0260] (6) stretching and consolidation: stretching the fiber web obtained in step (5), and then forming a nonwoven fabric with desired physical properties by thermal bonding and web laying;

[0261] Specifically, the parameters of the stretching in step (6) are as follows: the stretching ratio is 1.2 times, the stretching temperature is 40°C, and the stretching speed is 80 m / min; the parameters of the hot bonding in step (6) are as follows: the method is hot rolling, the roller temperature is 140°C, the roller pressure is 40 N / mm, and the roller gap is 0.1 mm.

[0262] (7) Post-treatment: heat treating and calendering the nonwoven fabric obtained in step (6);

[0263] Specifically, the parameters of the heat treatment in step (7) are as follows: temperature is 130°C, heat treatment time is 30s;

[0264] The parameters of the calendering treatment in step (7) are as follows: the calendering temperature is 100°C, the calendering pressure is 20 N / mm, the calendering time is 2s, and the calendering roller linear speed is 10 m / min.

[0265] Solution 5

[0266] The preparation process of modified non-woven fabric produced by recycling PP lunch box broken pieces includes the following steps:

[0267] (1) Raw material preparation: sort, clean and screen the recycled PP lunch box fragments, then mix them with the modified enhancer for later use;

[0268] Specifically, the sorting step in step (1) is as follows: pour the PP lunch box crushed pieces into clean water, stir and separate the floating PP lunch box crushed pieces; the cleaning step in step (1) is as follows: put the sorted PP lunch box crushed pieces into 80°C hot water, stir and clean; the screening step in step (1) is as follows: control the size of the cleaned PP lunch box crushed pieces within 10 mm through a crusher.

[0269] The mass of the modified strengthening agent added in step (1) is 15% of the PP lunch box crushed pieces;

[0270] The components of the modified reinforcing agent in step (1) include the following in parts by weight:

[0271] 40 parts of aminoacetic acid,

[0272] 10 parts of azobisisobutyronitrile,

[0273] 25 parts of polyethylene glycol;

[0274] The mixing pressure in step (1) is 4 MPa and the mixing temperature is 75°C.

[0275] The preparation method of the nanocomposite material is as follows:

[0276] Magnesium nitrate, ferrous sulfate, gadolinium nitrate, manganese nitrate and cobalt triacetylacetonate are ground and mixed in a mass ratio of 5:5:6:8:6, and 80 times the mass of imidazole-4-carboxylic acid of the mixture are added, and the mixture is stirred and reacted at 90°C for 16 hours. The precipitate is repeatedly rinsed with anhydrous ethanol, and then vacuum freeze-dried at -80°C for 24 hours. The obtained powder is transferred to a high-temperature calcination furnace and calcined at 600°C for 13 hours under a nitrogen environment, with a heating rate of 10°C / min.

[0277] (2) Feeding and conveying: using a screw feeder to convey the raw materials prepared in step (1) to the screw extruder;

[0278] Specifically, the screw feeder described in step (2) is a screw conveyor, and its pitch is 0.6 times the screw diameter.

[0279] (3) Screw extrusion: using a screw extruder to melt and extrude the raw materials in step (2);

[0280] The parameters of melt extrusion in step (3) are as follows:

[0281] Zone 1: 220℃,

[0282] Zone 2: 225℃,

[0283] Zone 3: 230℃,

[0284] Zone 4: 235℃,

[0285] Zone 5: 240℃,

[0286] Zone VI: 235°C.

[0287] (4) Spinning: Extruding the melt-extruded material in step (3) through a spinneret for spinning;

[0288] Specifically, the aperture of the spinneret in step (4) is 0.4 mm; the temperature of the spinneret in step (4) is 300° C.; the spinning speed of the spinneret in step (4) is 3500 m / min; and the fiber fineness range of the spun fiber in step (4) is 2.5 dtex.

[0289] (5) Cooling and solidifying: cooling and solidifying the fibers spun in step (4) by a cooling device, and forming a continuous fiber web after laying;

[0290] Specifically, the temperature reduction range of the cooling and curing in step (5) is 5°C / min; the termination temperature after cooling and curing in step (5) is 25°C; and the ambient humidity of the cooling and curing in step (5) is 60%.

[0291] (6) stretching and consolidation: stretching the fiber web obtained in step (5), and then forming a nonwoven fabric with desired physical properties by thermal bonding and web laying;

[0292] Specifically, the parameters of the stretching in step (6) are as follows: the stretching ratio is 3.5 times, the stretching temperature is 60°C, and the stretching speed is 150 m / min; the parameters of the hot bonding in step (6) are as follows: the method is hot rolling, the roller temperature is 160°C, the roller pressure is 80 N / mm, and the roller gap is 1.0 mm.

[0293] (7) Post-treatment: heat treating and calendering the nonwoven fabric obtained in step (6);

[0294] Specifically, the parameters of the heat treatment in step (7) are as follows: temperature is 160°C, heat treatment time is 120s;

[0295] The parameters of the calendering treatment in step (7) are as follows: the calendering temperature is 140°C, the calendering pressure is 100 N / mm, the calendering time is 10s, and the calendering roller linear speed is -100 m / min.

[0296] Test plan:

[0297] The nonwoven fabrics prepared in the above schemes 1-5 were subjected to the following tests:

[0298] Tensile strength and elongation at break: GB / T 3923.1, Tear strength: GB / T 3917.1, Bursting strength: GB / T19976, Air permeability: GB / T 5453.

[0299] Table 1 Comprehensive test

[0300]

[0301] As shown in the table above, the nonwoven fabric prepared by Scheme 3 performs best in various performance indicators such as tensile strength, elongation at break, tear strength, bursting strength, and air permeability. Through comparative analysis, it can be seen that the preparation process of Scheme 3 is the best under the premise of ensuring the mechanical properties and air permeability of the nonwoven fabric.

[0302] Among them, scheme 4 does not use modified reinforcing agent. Tensile strength: The tensile strength of scheme 4 is significantly lower than that of other schemes, only 40.2 MPa, while other schemes are all above 45 MPa. This shows that modified reinforcing agent has a significant effect on improving the tensile strength of the material. Elongation at break: The elongation at break of scheme 4 is the lowest, which is 360%, while other schemes are all above 400%. Modified reinforcing agent can increase the ductility of the material. Tear strength: The tear strength of scheme 4 is 245 N / mm, which is the lowest among all schemes. Modified reinforcing agent helps to improve the tear resistance of the material. Bursting strength: The bursting strength of scheme 4 is only 0.5 MPa, which is much lower than other schemes. This shows that modified reinforcing agent can significantly improve the impact resistance of the material. Air permeability: The air permeability of scheme 4 is 1540 cm³ / (m²·24h·0.1MPa), which is the lowest among all schemes. Modified reinforcing agent helps to form more microporous structures, thereby improving the air permeability of the material. In summary, Scheme 4 without the use of a modified reinforcing agent performs poorly in all performance indicators. The mechanism of action of the modified reinforcing agent includes: enhancing the intermolecular forces and improving the overall strength and toughness of the material. Improving the arrangement and cross-linking degree of the molecular chains and improving the ductility of the material. Forming a more uniform microstructure and improving the tear and impact resistance of the material. Introducing some microscopic pores or channels to improve the air permeability of the material. The combined effect of these modification effects makes the scheme with the addition of a modified reinforcing agent superior to Scheme 4 without the addition in all performance indicators. This also shows that when using recycled PP lunch box fragments to produce modified non-woven fabrics, the modified reinforcing agent plays a key role and is an important factor in improving product performance.

[0303] While Scheme 5 does not use nanocomposites, tensile strength: The tensile strength of Scheme 5 is 45.9 MPa, which is lower than that of Schemes 1-3, but higher than that of Scheme 4. This shows that nanocomposites can improve the tensile strength of materials by enhancing the interfacial bonding between the polymer matrix and the fibers. Elongation at break: The elongation at break of Scheme 5 is 400%, which is lower than that of Schemes 1-3. Nanocomposites improve elongation at break by improving the flexibility and ductility of polymer chains. Tear strength: The tear strength of Scheme 5 is 257 N / mm, which is lower than that of Schemes 1-3. Nanocomposites improve the tear resistance of materials by forming energy dissipation mechanisms in the microstructure. Bursting strength: The bursting strength of Scheme 5 is 0.7 MPa, which is lower than that of Schemes 1-3. Nanocomposites improve the bursting strength by enhancing the overall structural integrity and impact resistance of the material. Air permeability: The air permeability of Scheme 5 is 1620 cm³ / (m²·24h·0.1MPa), which is lower than that of Schemes 1-3. Nanocomposites improve air permeability by forming micropores in the material or changing the arrangement of fibers. The mechanism of action of nanocomposites includes: Nanoscale effect: Due to their extremely small size, nanoparticles can be evenly dispersed in the polymer matrix, providing a large amount of interface area, thereby enhancing the overall performance of the material. Interface interaction: The strong interaction between nanoparticles and polymer molecular chains can improve the mechanical properties and thermal stability of the material. Structural regulation: Nanoparticles affect the crystallization behavior and microstructure of polymers, thereby changing the physical properties of the material. Multifunctionality: Different types of nanoparticles can give materials specific functions, such as enhancing mechanical properties and improving flame retardancy. Pore structure regulation: Nanoparticles affect the pore structure of the material, thereby affecting air permeability and other related properties. In general, the addition of nanocomposites significantly improves the comprehensive performance of non-woven fabrics. Although Scheme 5 still shows good performance without the use of nanocomposites, all indicators have declined compared with the scheme using nanocomposites. This highlights the important role of nanocomposites in the preparation of modified non-woven fabrics.

[0304] In addition, the test of the sterilization of floating bacteria was carried out by mixing 1g of nonwoven fabric with 10mL of 10 6 CFU / mL of Escherichia coli (Escherichia coli O157: H7) bacterial solution was mixed, and a hydrogen peroxide solution with a final concentration of 10mM was added (the nanocomposite material can catalyze a small amount of hydrogen peroxide solution to produce hydroxyl free radicals to achieve a bactericidal effect), incubated for 1h, and then the plate dilution count was performed. Figure 5 As shown, the sterilization rate of Scheme 3 reached 99.6%, the sterilization rates of Scheme 1 and Scheme 2 were 80.9% and 91.4% respectively, while the sterilization rates of Scheme 4 and Scheme 5 were 1.1% and 22.4% respectively, which were almost incapable of sterilization.

[0305] Suggestions for follow-up research:

[0306] Establish quality control standards for recycling PP lunch box fragments:

[0307] Size requirements: The size of the broken pieces should be controlled within 5-10mm. If it is too large, it will affect the melting uniformity, and if it is too small, it will easily generate dust.

[0308] Impurity content: light impurities such as wood chips and paper scraps ≤ 0.05%, heavy impurities such as metals ≤ 0.01%.

[0309] Moisture content: ≤0.3%. Too high a content may easily lead to water vapor in the melt, affecting the spinning quality.

[0310] Odor: The broken pieces should have no peculiar smell and should be subjected to high-temperature deodorization treatment if necessary.

[0311] Optimizing crushing process

[0312] It adopts two-stage crushing: coarse crushing (20-30mm) + fine crushing (5-10mm) to reduce dust generation.

[0313] Metal detection and dust removal are carried out simultaneously during the crushing process to improve the purity of the crushed materials.

[0314] The crushed material can be surface modified as needed, such as plasma treatment, to improve its compatibility with PP.

[0315] Optimize the proportion of ingredients

[0316] Depending on the quality requirements, the amount of recycled PP flakes can be 30-70% and blended with virgin PP.

[0317] If necessary, add toughening agents, nucleating agents and other additives to improve the mechanical properties of the product.

[0318] Optimizing the melt extrusion process

[0319] A twin-screw extruder is used to improve the dispersion and mixing effect of the crushed materials.

[0320] Optimize the design of screw assembly components, such as using multiple sets of dispersion discs to enhance melt homogenization.

[0321] Increase back pressure, refine melt flow channels, and suppress bubbles generated by crushed materials.

[0322] Optimizing the spinning process

[0323] Lower the spinning temperature to minimize thermal degradation of the crushed PP.

[0324] A high-efficiency filtration system is used to reduce the blockage of the spinneret by impurities in the crushed materials.

[0325] Optimize cooling and drawing conditions to improve fiber orientation and uniformity.

[0326] Optimizing the laying and forming process

[0327] Use multi-lay mesh heads to improve the uniformity of the fiber web.

[0328] Optimize hot rolling temperature and pressure, and reduce them appropriately when crushing PP products with low melting points.

[0329] After hot rolling, online dust removal is used to remove dust particles on the surface of the fiber web.

[0330] Strengthen quality inspection

[0331] Establish a quality inspection system for raw materials, semi-finished products and finished products.

[0332] Focus on key indicators such as fiber diameter, strength and uniformity.

[0333] Surface quality, feel, smell, etc. are rigorously evaluated.

[0334] Through the optimization of the above production process, we can make full use of recycled PP lunch box scraps to produce high-quality spunbond non-woven fabrics, while reducing raw material costs, realizing the recycling of plastic resources and promoting the green and sustainable development of the industry.

[0335] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A process for preparing a modified nonwoven fabric produced by recycling PP lunch box fragments, comprising the steps of: 1) Raw material preparation: sort, clean and screen the recycled PP lunch box fragments, and then mix them with the modified enhancer; 2) Feeding and conveying: using a screw feeder to convey the raw materials prepared in step 1) to the screw extruder; 3) Screw extrusion: using a screw extruder to melt and extrude the raw materials in step 2); 4) Spinning: The melt-extruded material in step 3) is extruded through a spinneret for spinning; 5) Cooling and solidification: The fibers spun in step 4) are cooled and solidified by a cooling device, and a continuous fiber web is formed after laying; 6) Drafting and reinforcement: The fiber web obtained in step 5) is drafted, and then formed into a non-woven fabric by thermal bonding and web laying; 7) Post-treatment: heat treatment and calendering treatment of the non-woven fabric obtained in step 6); In step 1), the sorting step is as follows: pouring the crushed pieces into clean water, stirring and separating the floating crushed pieces; washing step is as follows: putting the sorted crushed pieces into 60-80°C hot water, stirring and washing; screening step is as follows: controlling the size of the washed crushed pieces within 10mm by a pulverizer; the mixing pressure is 2-4MPa and the temperature is 65-75°C; the mass of the modified reinforcing agent added is 10-15% of the crushed pieces, calculated by weight, and includes: 25-40 parts of aminoacetic acid, 10-20 parts of nanocomposite material, 5-10 parts of azobisisobutyronitrile, and 15-25 parts of polyethylene glycol; The preparation method of the nanocomposite material is as follows: Magnesium nitrate, ferrous sulfate, gadolinium nitrate, manganese nitrate and cobalt triacetylacetonate are ground and mixed in a mass ratio of (1-5): (1-5): (3-6): (2-8): (1-6), and imidazole-4-carboxylic acid in an amount of 50-80 times the mass of the mixture is added, and the mixture is stirred and reacted at 80-90°C for 8-16 hours. The precipitate is repeatedly rinsed with anhydrous ethanol, and then vacuum freeze-dried at -80°C for 24 hours. The obtained powder is transferred to a high-temperature calcination furnace and calcined at 400-600°C for 9-13 hours in a nitrogen environment, with a heating rate of 10°C / min.

2. The process for preparing modified nonwoven fabrics produced by recycling PP lunch box fragments according to claim 1, characterized in that: The screw feeder described in step 2) is a screw conveyor, and its pitch is 0.5 to 0.6 times the screw diameter.

3. The process for preparing modified nonwoven fabric produced by recycling PP lunch box fragments according to claim 1, characterized in that: The parameters of melt extrusion in step 3) are as follows: Zone 1: 215-225℃, Zone 2: 220-230℃, Zone 3: 225-235℃, Zone 4: 230-240℃, Zone 5: 235-245℃, Zone VI: 230-240℃.

4. The process for preparing modified nonwoven fabric produced by recycling PP lunch box fragments according to claim 1, characterized in that: In step 4), the aperture of the spinneret is 0.2-0.4 mm; In step 4), the temperature of the spinneret is 280-300°C; In step 4), the spinning speed of the spinneret is 1500-3500 m / min; The fiber fineness range of the spun fiber in step 4) is 1.0-2.5 dtex.

5. The process for preparing modified nonwoven fabric produced by recycling PP lunch box fragments according to claim 1, characterized in that: In step 5), the temperature reduction range of cooling and solidification is 5°C / min; In step 5), the final temperature after cooling and solidification is 25°C; The ambient humidity during cooling and curing in step 5) is 60%.

6. The process for preparing modified nonwoven fabric produced by recycling PP lunch box broken pieces according to claim 1, characterized in that: The drafting parameters in step 6) are as follows: The drafting ratio is 1.2-3.5 times, the drafting temperature is 40-60℃, and the drafting speed is 80-150 m / min; The parameters for hot gluing in step 6) are as follows: The method is hot rolling, the roll temperature is 140-160°C, the roll pressure is 40-80 N / mm, and the roll gap is 0.1-1.0 mm.

7. The process for preparing modified nonwoven fabric produced by recycling PP lunch box fragments according to claim 1, characterized in that: The parameters of the heat treatment in step 7) are as follows: The temperature is 130-160°C and the heat treatment time is 30-120s; Step 7) The parameters of the calendering treatment are as follows: The calendering temperature is 100-140°C, the calendering pressure is 20-100 N / mm, the calendering time is 2-10s, and the calendering roller linear speed is 10-100 m / min.

Citation Information

Patent Citations

  • Electret master batch for melt-blown cloth and preparation method and application of electret master batch

    CN111718540A

  • Alloy powder and preparation method and application thereof

    CN113649565A